Decision Support Tools for Selecting Organisational Improvement Initiatives: a Review - Mohammad, Musli; Manni Vattiyan, Ligesh; Shahir Yahya, Mohd (International Journal of Engineering and Technology, 2018)
Decision support tools are used in many organisations to support organisational decision making activities. However, very limited studies have been found focussing on the decision support tools for selecting organisational improvement initiatives. Improvement initiatives are approaches, management systems, tools and/or techniques that can be used for managing and improving organisations, such as Lean, ISO9001 and Improvement Team. Four existing decision support tools were reviewed and compared. All four decision support tools consist of decision matrix, rating and ranking to assist in selecting appropriate improvement initiative. Finally, several potential future studies have been proposed.Â Â